Papillary fibroelastoma, unusual cause of stroke in a young man: a case report - Elisabetta Grolla; Michele Dalla Vestra; Giampaolo Zoffoli; Riccardo D’Ascoli; Adriana Critelli; Rocco Quatrale; Domenico Mangino; Fausto Rigo (Journal of Cardiothoracic Surgery, 2017)
Abstract Background Papillary fibroelastoma is the third most common primary benign tumor with an incidence of up to 0.33% in autopsy series; it accounts for approximately 75% of all cardiac valvular tumors. Case presentation We describe a rare case of a 28-Year-old man that while playing football, had a sudden onset of neurological deficit: aphasia, right hemiparesis and right facial numbness. Transthoracic echocardiography (TTE) showed a 10x10 mm mass attached to the anterior mitral valve leaflet. The patient was treated surgically for the prevention of further embolic complications. Histologic examination of the resected mass revealed a papillary fibroelastoma. It is the third most frequent primary cardiac tumor, after myxoma and fibroma, and the most common primary tumor of heart valves. Despite the benign nature of this tumor, it carries very high risk of embolic complications. The successful complete resection of the papillary fibroelastoma is curative and the long-term postoperative prognosis is excellent. Conclusions Differential diagnosis of cardiac masses requires clinical informations, laboratory tests, blood cultures and appropriate use of imaging modalities. Papillary fibroelastoma is a potential cause of embolic stroke in the young. The prompt surgical excision of papillary fibroelastoma is curative and the long-term postoperative prognosis is excellent.